Study guides

Q: Factor x2 plus 13x plus 36 completely?

Write your answer...

Submit

Related questions

(x + 9)(x + 4)

(x-4)(x-9)

6(13x + 6)

(x + 4)(x + 9)

(x + 9)(x + 4)

(x-4)

The factors of x2-13x+36 are 'x-9' and 'x-4'because the expression (x-9)(x-4) can be simplified as x2-13x+36.

x2-13x+36 = (x-4)(x-9) when factored

If that's plus 36, it factors to (x - 9)(x - 4) If it's minus 36, it gets ugly in a hurry.

x2 + 13x + 36 = 0 so (x+4)(x+9) = 0 so that x = -4 or x = -9

x2-13x+36=(x-9)(x-4)=0 x=9 or x=4

(x - 9)(x - 4)

(x+9)(x+4)

n^2(n + 6)(n^2 - 6n + 36)

Well, if that was a - 13X we could factor by inspection, but now the quadratic formula is needed. By inspection the discriminant yields two real roots. X^2 + 13X + 36 = 0 X = - b (+/-) sqrt(b^2-4ac)/2a a = 1 b = 13 c = 36 X = - 13 (+/-) sqrt[b^2 - 4(1)(36)]/2(1) X = - 13 (+/-) sqrt(169 - 144)/2 X = - 13 (+/-) sqrt(25)/2 X = [- 13 (+/-) 5]/2 X = - 4 ------------ X = - 9 -----------

x-4 is the correct answer for Apex

To factorise this completely you need to be aware that 216 = 63. (x3 + 216) = (x + 6)(x2 - 6x + 36)

x^2 - 13x + 36 = 0 Factor: (X-9)(X-4) = 0 X = 9 X = 4

x(x2 + 36)

2(x + 6)(x + 3)

the greatest common factor is 4 plus 36 has non

I'm guessing that's x2 + 13x + 36. So you're looking for two factors of 36 whose sum is 13. It's not 36 and 1, 18 and 2, 12 and 3 or 6 and 6. (x + 4)(x + 9)

6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)

x2 + 36 cannot be factored. You can only factor the difference of two squares, not the sum.

x squared minus 12 x plus 36 = (x - 6)(x - 6)